41=29-2(x-2)

Simple and best practice solution for 41=29-2(x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 41=29-2(x-2) equation:



41=29-2(x-2)
We move all terms to the left:
41-(29-2(x-2))=0
We calculate terms in parentheses: -(29-2(x-2)), so:
29-2(x-2)
determiningTheFunctionDomain -2(x-2)+29
We multiply parentheses
-2x+4+29
We add all the numbers together, and all the variables
-2x+33
Back to the equation:
-(-2x+33)
We get rid of parentheses
2x-33+41=0
We add all the numbers together, and all the variables
2x+8=0
We move all terms containing x to the left, all other terms to the right
2x=-8
x=-8/2
x=-4

See similar equations:

| 2(×+1)/6=3x-5 | | z+4/7=-2 | | m/9+4=7 | | -31=-6n-7 | | 54²=6s² | | 5x^2-3=10x+12 | | 3d+8=2d-17= | | (2x+1/3)+x+5=(3x+1/8) | | 5+1/7(b)=-2 | | l/4-3=-2 | | (8x/3)-4=12 | | B=73.14f | | 5/2x-x=-30 | | 4x-9x=4x+40 | | 2w+10=w+25 | | 85y=14(6y+19) | | 2m/3-m/5=4 | | 2x-11=3x+3-8x | | 3/2x+2x=1/2x+3 | | 2(w-6)=4w-10 | | 2-16t=6(—3t+2) | | -2x-14=9(x-4) | | 2(y-6)=-3y-27 | | 3(2-x/4)=2(1-x/3) | | 3(f-3)=5(2f+1) | | 47-x=286 | | 3/x^2-9+6/x^2=3x-18 | | 1/3k-5=2 | | -6x+36=-24 | | 3x^2+80x-11500=0 | | (18-y)+5y=58 | | 142=193-w |

Equations solver categories